2018
DOI: 10.1108/jkm-06-2017-0219
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge centricity and organizational performance: an empirical study of the performing arts

Abstract: Purpose This paper explores the concepts of knowledge-centric organizations in the performing arts sector to understand how specific organizational practices relate to measures of financial and operational performance. Design/methodology/approach A quantitative analysis of 368 small and mid-sized nonprofit performing arts organizations in the USA was undertaken via primary data on organizational practices and secondary data on performance metrics. Structural equation modeling was used to validate the latent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…The third study addressing relational capital (Álvarez-González et al, 2017) looked at NPOs more broadly and showed that competition among NPOs and business firms improves the effectiveness of the organization, in terms of obtained funding (financial performance), provided services, and reached users (mission-based performance). Finally, a study reorganized the dimensions of IC into a new construct, namely the knowledge centricity (Vakharia et al, 2018). Knowledge centricity includes a hard and a soft dimension.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The third study addressing relational capital (Álvarez-González et al, 2017) looked at NPOs more broadly and showed that competition among NPOs and business firms improves the effectiveness of the organization, in terms of obtained funding (financial performance), provided services, and reached users (mission-based performance). Finally, a study reorganized the dimensions of IC into a new construct, namely the knowledge centricity (Vakharia et al, 2018). Knowledge centricity includes a hard and a soft dimension.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…One out of nine papers only addressed the human dimension (Cady et al, 2018), whereas three papers addressed the relational dimension (Misener and Doherty, 2013;Wemmer et al, 2016;Álvarez-González et al, 2017), and one paper addressed both human and structural/organizational capital (Zhu et al, 2016). Finally, one paper took into account dimensions related to the types of knowledge tackled in the IC framework but reorganized them in the knowledge-centricity construct (Vakharia et al, 2018).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Competence that is manifested in the form of credibility and good character can affect the society's trust towards the LPD. As a financial institution that is established and developed based on the custom, LPDs need to strengthen their internal management by enhancing management professionalism, while maintaining their custom based nature but balanced with the knowledge of modern organizations (Vakharia et al, 2018). Lindner (2001) stated that competence has a significant influence on performance.…”
Section: Introductionmentioning
confidence: 99%